Persepsi Netizen Indonesia di Media Sosial TikTok Kompas.com terhadap Wafatnya Paus Fransiskus - Bella Aulia; Nuraida; Sri Hertimi (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2026)
This study examines the perceptions of Indonesian netizens on the Kompas.com TikTok social media platform regarding the death of Pope Francis, who passed away on April 21, 2025. The death of Pope Francis was a global event that also stirred the Indonesian digital space, particularly in the comment sections of the Kompas.com TikTok account, giving rise to diverse dynamics of religious tolerance. As a multireligious country, Indonesia faces its own challenges in maintaining interfaith harmony, and social media platforms such as TikTok have become highly dynamic public spaces in shaping public perceptions toward religious figures across different faiths. This study aims to determine how Indonesian netizens perceive the death of Pope Francis, particularly in relation to the value of religious tolerance. The research method employed was qualitative research using a netnographic approach with a descriptive methodology. Primary data was collected through documentation of comments on the Kompas.com TikTok account between April 21 and May 12, 2025. Data analysis was conducted using the Miles and Huberman model through the stages of data reduction, data presentation, and conclusion drawing, grounded in the Theory of Planned Behavior. The findings reveal that Indonesian netizens' perceptions fall into three categories: positive, negative, and neutral comments. Positive comments reflect a high level of tolerance, with the majority of Muslim netizens respecting Pope Francis as a symbol of universal humanity. Negative comments reflect a lack of empathy, such as inappropriate jokes. Meanwhile, neutral comments proved to be the most meaningful voices, as they reflect religious moderation alive within the digital space. Overall, this study concludes that the majority of Indonesian netizens, particularly Muslims, possess a high level of tolerance maturity, making humanitarian values a bridge that transcends theological differences, in line with the spirit of Islam rahmatan lil 'alamin. This study is expected to enrich the study of digital communication regarding netizen behavior in responding to sensitive religious issues in the public sphere.